2007
DOI: 10.4049/jimmunol.178.7.4097
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Induces the Expression of IL-1α in Colon Cancer Cells

Abstract: PGE2 has been shown to exert pro-oncogenic effects in colorectal neoplasia through producing autocrine or paracrine growth factors. In the present study, we demonstrate that PGE2 induced the expression of IL-1α in colon cancer cells, which plays critical roles in tumor metastasis and neoangiogenesis in a variety of cancers. PGE2 increased the levels of both IL-1α mRNA and protein, suggesting a positive feedback loop between the IL-1 pathway and PGE2 signaling. Mechanistically, PGE2 induced the expression of IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…The role of the EP2 receptor in mediating these effects was further confirmed using the selective EP2 agonist butaprost. This is consistent with similar study by Shao et al (2007) where it was shown that PGE 2 , acting via EP2 receptor activate cAMP/PKA pathway to mediate the expression of IL-1α in colon cancer cells in an autocrine/paracrine mechanism [18]. EP2 and its signaling have been found to be up-regulated in cervical cancer [9] and its role in the induction of IL-1α in cervical cancer could explain the greater expression of IL-1α in cervical cancer tissue explant relative to normal cervical tissue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The role of the EP2 receptor in mediating these effects was further confirmed using the selective EP2 agonist butaprost. This is consistent with similar study by Shao et al (2007) where it was shown that PGE 2 , acting via EP2 receptor activate cAMP/PKA pathway to mediate the expression of IL-1α in colon cancer cells in an autocrine/paracrine mechanism [18]. EP2 and its signaling have been found to be up-regulated in cervical cancer [9] and its role in the induction of IL-1α in cervical cancer could explain the greater expression of IL-1α in cervical cancer tissue explant relative to normal cervical tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Once released, IL-1α can act in an autocrine/paracrine manner within the site of production to regulate inflammation and tumorigenesis. Indeed, Shao and colleagues showed in their study that IL-1α stimulates the migration of colon cancer cells [18]. It is therefore plausible that in sexually active women with underlying pre-invasive or invasive cervical condition, repeated exposure of the elevated EP2 receptor expressed on the neoplastic cervical epithelial cells [9] to PGE 2 present in seminal plasma could enhance tumorigenesis following ligand-receptor binding and activation of similar intracellular signaling pathway to induce IL-1α expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IL1A gene encoding IL-1a is targeted by miR-122 and miR-378 , and IL-1a mRNA and protein have been detected in highly metastatic colon cancer cells (Matsuo et al, 2009). In addition, knocking down the expression of IL-1a leads to a reduction of vascular endothelial growth factor secretion in colon cancer cells (Shao and Sheng, 2007). Taken together, these findings indicate that miR-122/miR-378 and their target gene IL1A potentially play a role in CRC tumorigenesis.…”
Section: Discussionsupporting
confidence: 54%
“…IL-1b is present in the circulation of patients undergoing infectious or inflammatory responses, whereas IL-1a is rarely found in the circulation [6]. Voronov et al [7] demonstrated the critical roles of IL-1 in tumor invasiveness and angiogenesis in vivo, and many reports demonstrated the importance of IL-1 in colon cancer progression [8][9][10][11][12]. We have previously reported that IL-1a acts through its type I receptor (IL-1RI) to play an important role in invasive and angiogenic behaviors in pancreatic cancer cell lines, and confirmed that only those cancer cell lines highly metastatic to the liver express IL-1a mRNA [13][14][15].…”
Section: Introductionmentioning
confidence: 99%